PENDAMPINGAN USAHA PADA IBU– IBU SINGLE PARENT DALAM UPAYA PRODUKSI JAJANAN SEHAT DAN HALAL - Wahyuni, Wahyuni; Dewi Noorratri, Erika; Uswatun Khasanah, Aulia; Wiyono, Teguh (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Being a single parent mother is not easy, so single parent mothers must have the ability and resilience to carry out their duties as head of the household as well as a housewife. The need for persistent struggle to raise, care for, nurture and provide for their children alone. Other problems that need to be faced by a single parent are economic problems and caring for their children without the help of a partner, so the need for self-ability to be able to rise from the pressures and trials faced. This ability is proven by efforts both individually and in groups, so that it will have a positive impact, especially in dealing with economic problems, but this does not discourage single parent mothers who are members of the “Amanah” UMKM. They rise up how to survive even though the situation is uncertain, it becomes a trigger for independent entrepreneurship with business. The implementation of the Community Partnership Empowerment Program (PKM) begins with the socialization of the program at the home of the head of MSME “Amanah” Mrs. Wagiyati 44 years old in Parangjoro Village Rt, 01/03 Grogol District, Sukoharjo Regency and its members conduct interviews and discussions and to provide input on this Community Partnership Empowerment Program (PKM) and has been agreed between the chief executive and the head of MSME “Amanah” and includes training in the use of electric flour dough kneading machines, assistance in the use of P machines. Assistance in the use of electric sausage and lumpya filling meat grinding machines, assistance in the use of oil draining machines, assistance in the use of vaccum machines for product packaging, labeled product packaging and packing training, marketing management and MSME management training, financial management training and making simple financial reports, halal certified product registration, producing a scientific journal Gemassika